Nuclease-Treated Stabilized Fermentation Product of Cetobacterium somerae Improves Growth, Non-specific Immunity, and Liver Health of Zebrafish (Danio rerio) - Xie, Mingxu; Hao, Qiang; Xia, Rui; Olsen, Rolf Erik; Ringø, Einar; Yang, Yalin; Zhang, Zhen; Ran, Chao; Zhou, Zhigang (Frontiers in Nutrition, 2022)
High-fat diets (HFD) are harmful to fish health. Probiotics are commonly utilized to improve fish nutrition metabolism, immune response, and health. Nucleic acids of the probiotic bacterium can be hydrolyzed by nuclease to generate nucleotides. The present study aimed to evaluate the effects of stabilized fermentation product of nuclease-treated Cetobacterium somerae XMX-1 (XMX-1(N)) on growth, non-specific immunity, and liver health of zebrafish. Compared to the HFD group, 100 g/kg XMX-1 (N) significantly increased weight gain and decreased feed conversion ratio (FCR). However, 5 g/kg or 10 g/kg XMX-1 (N) had no influence on zebrafish growth. In addition, supplementation of 100 g/kg XMX-1(N) significantly increased lysozyme activity and total antioxidant capacity in skin mucus, and the expression of inflammation related genes interleukin 1 beta (IL-1β), interleukin 10 (IL-10), and interleukin 6 (IL-6) in the gut as well as fatty acid oxidation related genes uncoupling protein 2 (UCP2) and proliferator-activated receptor γ coactivator 1α (PGC1α) in the liver, while decreased the content of hepatic triacylglycerol (TAG) in zebrafish. 16S rRNA gene sequencing showed that 100 g/kg XMX-1(N) enhanced the relative abundance of Firmicutes while lowered Proteobacteria and Actinobacteria. 10 g/kg XMX-1(N) significantly increased lysozyme activity and complement component 4 (C4) in skin mucus, and intestinal expression of inflammation-related genes. In the 5 g/kg XMX-1(N) group, however, only an increase in C4 level in skin mucus was observed. Together, these results reveal that dietary supplementation with nuclease-treated C.somerae XMX-1 (N) has a dose-dependent beneficial effect on fish health.